Word Recognition Test for Iraqi-Speaking Adults - Ali Ismail Qasim; Sami Raheem Al-Katib; Yasir Lafta Hassoun; Jaafar Ismail Qasim (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: to contribute in the development of speech audiometric test in Iraq by using Arabic-Iraqi dialectfor measuring word recognition score (WRS).Methods: sixty normal persons aged 40-65 years (30 males and 30 females) divided into six equal groups.After determining hearing thresholds (PTA) determine WRS , each list of 25 words to one group, monaurallyin the better ear at several intensities through speech audiometer by using monosyllable Alusi’s words liststhrough monitored live voice (MLV).Results: the normal speech audiometric curves of word recognition test in this study are similar to thenormal curves obtained with previous Arabic, European and American monosyllabic word lists in additionto no intelligibility differences between Alusi’s monosyllable word half-lists.Conclusion: this study suggests Alusi’s monosyllable word lists can be used in Iraqi Arabic-speaking adultsto determine WRS.